Science Education in Ghana (Journal of Science and Technology, 2016)
Fundamentally, science involves knowledge about elements, forces and processes of nature. This paper seeks to establish that our environment is very rich in. these elements, forces and processes of nature. Some, of these have been recognized and interpreted in many areas of our society and some are of valuable service to us. Even though the present state of scientific knowledge within our context May be intuitive or rudimentary and may be sometimes contrary to modem scientific knowledge; nevertheless, the infrastructure is there and the Ghanaian child must be 'made aware of the scientific and learning potential of his rich environment this is Education through science.